Clarifying the Correlation of Ice Adhesion Strength with Water Wettability and Surface Characteristics - Wu, Xinghua (Langmuir : the ACS journal of surfaces and colloids, 2020)
Although icephobic surfaces have been extensively investigated in the past decades, a controversy remains on the relationship between water repellency and ice repellency. Little insight has been truly obtained on the dependence of ice adhesion on the surface/interface characteristics because of the limited range of these characteristics that have been investigated in the past. In this study, we prepared 37 coatings with a wide range of surface characteristics. The measured ice adhesion strength was discussed in correlation with water wettability and surface topological parameters. It was verified that parameters related to water wettability, such as water contact angle, contact angle hysteresis, and an index of work of adhesion with water, (1 + cos θrec), do not have a simple correlation with ice adhesion strength. Thus, they should not be used as a design parameter for low icephobic surfaces. The current study points out that the study of surface texture should be carried out in conjunction with surface chemistry/energy consideration. Without control of the surface chemistry, the correlation between surface texture parameters will lead to inconsistent conclusions because of the uncertainty of the contact mode. Our investigation indicates that low ice adhesion strength (<50 kPa) is attainable with a smooth surface (root-mean-squared roughness < 50 nm) when a low surface energy (<15 mJ/m2) is maintained. This finding opens a new paradigm for the design of icephobic coatings away from the conventional practices of using superhydrophobic and oil-infused surfaces